Association of Homa-IR and Small Dense LDL to Determine IR in Young Obese Type 2 Diabetic Subjects in Both Sex - Richhariya, Amrita; Singh, Neelima (Indian journal of clinical biochemistry, 2022)
The formation of sdLDL is increased in the presence of insulin resistance and dyslipidemia in diabetic subjects. Type 2 diabetes mellitus now-a-days, also known as low grade chronic inflammatory disease especially when it is associated with obesity. Obesity-induced insulin resistance is associated with increased lipid concentrations in insulin-responsive tissues, normal glucose tolerant people with enlarged subcutaneous abdominal adipocytes and elevated levels of FFA which are at increased risk of developing T2DM. IR also appears to play an important role in the pathogenesis of this type of dyslipidemia. Our study aims to investigate the association of Homa-IR and small dense LDL in Young obese type II diabetic subjects in both sexes. This study was carried out in Department of Biochemistry, G.R.Medical College, Gwalior and part of the work in Laboratory Medicine, Department of Biochemistry, Medanta-The Medicity Hospital, Gurgaon. 100 known type 2 diabetic subjects (M & F) with age 24-40 years were included in the study and 100 were healthy control, age matched having normal body mass index (BMI). Statistical analysis was done using multiple regressions which has proved the above relationship between IR and obesity. sdLDL was positively associated with Homa-IR (p < 0.05), TG (p < 0.01), LDL-C (p < 0.01), VLDL-C (p < 0.01) and TC/ HDL-C ratio (p < 0.01) while, negatively associated with cholesterol level (p < 0.01) and HDL-C (p = NS) in young obese group (both sex). The study shows that, obesity in young age is main precipitating factor for insulin resistance and high insulin resistance block the way for the utilization of glucose and thus, precipitates the diabetes mellitus, hence, these findings justify that obesity in type 2 diabetics is associated with hyperinsulinemia, hyperlipidaemia and glycemic conditions which are more prone for CVDs in young diabetic population.